Effectiveness of the E2-Classical Swine Fever Virus Recombinant Vaccine Produced and Formulated Within Whey from Genetically Transformed Goats - Cortez-San Martin, M (American Society for Microbiology, 2014)
Subunit recombinant vaccines against classical swine fever virus (CSFV) are a promising alternative to overcome practical and biosafety issues with inactivated vaccines. One of the strategies in evaluation under field conditions is the use of a new marker E2-based vaccine produced in the milk of adenovirally transduced goats. Previously we had demonstrated the efficacy of this antigen, which conferred early protection and long-lasting immunity in swine against CSFV infection. Here, we have used a simpler downstream process to obtain and formulate the recombinant E2 glycoprotein expressed in the mammary gland. The expression levels reached approximately 1.7 mg/ml, and instead of chromatographic separation of the antigen, we utilized a clarification process that eliminates the fat content, retains a minor amount of caseins, and includes an adenoviral inactivation step that improves the biosafety of the final formulation. In a vaccination and challenge experiment in swine, different doses of the E2 antigen contained within the clarified whey generated an effective immune response of neutralizing antibodies that protected all of the animals against a lethal challenge with CSFV. During the immunization and after challenge, the swine were monitored for adverse reactions related to the vaccine or symptoms of CSF, respectively. No adverse reactions or clinical signs of disease were observed in vaccinated animals, in which no replication of CSFV could be detected after challenge. Overall, we consider that the simplicity of the procedures proposed here is a further step toward the introduction and implementation of a commercial subunit vaccine against CSF. Copyright © 2014, American Society for Microbiology. All Rights Reserved.